2021
DOI: 10.1002/lsm.23417
|View full text |Cite
|
Sign up to set email alerts
|

On‐Site Laser Photobiomodulation Treatment of Crushed Muscle Due to Prolonged Pressure in Rats

Abstract: Background and Objectives: Crush injuries and prolonged pressure on muscles lead to bruises and sprains and, in most of the cases, cause distraction of the muscle and release of particles into the blood stream, causing renal and systemic complications in severe cases. Laser photobiomodulation treatment (i.e., laser phototherapy) is a method suggested to decrease the pressure damage in the first 24-48 hours after muscle injury, allowing a faster and more complete physical rehabilitation. We studied the efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The efficacy of the laser photobiomodulation treatment after crushed muscle injury to the gastrocnemius muscle in a rat model was evaluated. 12 The study results showed a significant recovery of the gastrocnemius muscle during the first 3 days, the most critical clinical period, after the induction of the muscle crushed injury. The findings suggest that the therapeutic approach may help restore the muscle after crush injury.…”
Section: Phototherapy For Repair Of Musclementioning
confidence: 82%
“…The efficacy of the laser photobiomodulation treatment after crushed muscle injury to the gastrocnemius muscle in a rat model was evaluated. 12 The study results showed a significant recovery of the gastrocnemius muscle during the first 3 days, the most critical clinical period, after the induction of the muscle crushed injury. The findings suggest that the therapeutic approach may help restore the muscle after crush injury.…”
Section: Phototherapy For Repair Of Musclementioning
confidence: 82%
“…As one of the hottest growing areas in biomedical sciences [6], Photobiomodulation (PBM) has been extensively used in different therapeutic areas [7] like crushed muscle [8], nervous system [9], Alzheimer's disease [10] and cancer [11]. What calls for special attention is that different optical parameters may lead to different treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%